(untitled) (Voice of Culture, 2022)
नेवार काठमाडौं उपत्यकाको प्राचीन एवम् प्रमुख निवासी हुन् । धार्मिक दृष्टिकोणले नेवार समुदाय हिन्दू र बौद्ध दुई सम्प्रदायमा आवद्ध छन् । हिन्दूमार्गीमा ब्राह्मण, क्षेत्री, वैश्य र शुद्र चार वर्ण एवम् त्यसअन्तर्गत विभिन्न जातहरु रहेका छन् भने बौद्धमार्गीमा हिन्दूहरुको जस्तो तहयुक्त वर्ण व्यवस्था रहेको छैन तर पेशा अनुसार जाति व्यवस्था कायम भएको छ । हिन्दूमार्गीमा पुरोहितको कार्य ब्राह्मणवर्गको राजोपाध्याय र द्यःबम्र्हूद्वारा गर्दछ भने बौद्धमार्गीमा गुभाजु (वज्राचार्य) ले गर्दछ । मानव जीवनमा जन्मदेखि मरणसम्म विभिन्न संस्कारहरु सम्पन्न गरिन्छन् । जीवनको अन्त्यमा गरिने संस्कार अन्त्येष्टि संस्कार हो । नेवार समुदायमा अन्त्येष्टि संस्कार गर्नको लागि सनां गुठी, सी गुठी र बीचाः गुठीको व्यवस्था भएको छ । मृत्युको भय, मृत्युपछिको जीवनको सिद्धान्त, भय र स्नेहमिश्रित भावनाहरु र शारीरिक आवश्यकतालाई अन्त्येष्टि संस्कारको उद्भवको कारण मानिएको छ । नेवार समुदायमा अन्त्येष्टि संस्कारमा विविध मौलिकक्रियाहरु गरिन्छन् जस्तै– सिकया ब्व राख्ने, पाखाजा खाय्गु, न्हय्नुमा, जाप्वखाय्गु आदि । यी क्रियाहरु गर्नुको पछाडि अन्त्येष्टि संस्कारको उद्भवको कारणहरु रहेका छन् । Newar are early and chief inhabitants of Kathmandu Valley. From the aspect of religion, Newar community consists mainly two sect, Hinduism and Buddhism. Among Hindu Newars, there are four Varna (social class), Brahman, Chetri, Vaishya and Shudra along with different castes within these Varnas while in Buddhist Newars there are no such classes of Varnas like that of Hindu Newars. There is caste system on the basis of occupation in Buddhist Newars Rajopadhyay and Dhwobarmhu are the priests among Hindu Newars where as Gubhaju are the priests in Buddhist Newars. Many sacraments are conducted throughout the birth till the death of a human life. The sacraments performed at the end of a human life is called as Death Rites. There are provisions of Sanaa Guthi, Sii Guthi and Bichaa Guthi to deal with death rites in Newar Community. The fear of death, the concept of life after death, the fear and love for the dead person and the need to manage physical remains of the dead are considered a few reasons for conductingdeath rites. Newar community have different unique activities related to death rites, for example: offering Sikayaa bwo, hanging Pakhajaa, offering Nhyenuma and Jaapwon khayegu etc. for the deceased. The reason behind conducting these kinds of unique activities is the factors that originated the culture of death rites.